Analisis Struktur Kristal dan Morfologi Polikristalin La0,7Ba0,3Mn(1-x)FexO3 (x = 0; 0,1; 0,2; 0,25) dengan Metode Sintesis Sol-Gel Pembakaran Otomatis Sitrat-Nitrat - Ryka Usnilawaty; Budhy Kurniawan (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2025)
Polycrystalline La0.7Ba0.3Mn(1-x)FexO3 (x=0, 0.1, 0.2, 0.25) has been successfully synthesized using the sol-gel citrate-nitrate auto combustion method, with the high purity basic materials of La2O3, Ba(NO3)2, Mn(NO3)2.4H2O, Fe2O3, and C₆H₈O₇.H₂O as reaction fuel. After the gel was formed, the sample was heated at 180oC for 2.5 hours. Calcination was carried out at 800oC for 2 hours. Then the sample was compressed with a pressure of 10 tons, the sample was sintered at a temperature of 900oC for 2 hours. X-Ray Diffraction (XRD) analysis data shows a single phase in the four samples. SEM analysis data shows that the morphology of the particle diameter becomes smaller as the Fe is being added to the Mn site. EDS analysis data shows the element content in the four samples which is in accordance with stoichiometric calculations, and confirms that the product resulting from the sol-gel synthesis is homogeneous. The calculation of Goldschmidt tolerance factor has confirmed that the crystal structure is rhombohedral perovskite structure (0.929, 0.934, 0.939, and 0.941). Keywords: Lanthanum Manganites, Sol-Gel, Polycrystalline, Morphology, Rhombohedral.